2016
DOI: 10.3855/jidc.8206
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D level is associated with mortality predictors in ventilator-associated pneumonia caused by Acinetobacter baumannii

Abstract: Introduction: Vitamin D plays a role in host defense and is known to be associated with mortality in patients in the intensive care unit (ICU). We aimed to evaluate the relationships between vitamin D levels and predictors of mortality in patients with ventilator-associated pneumonia (VAP) caused by extensively drug-resistant Acinetobacter baumanii (XDR A. baumanii). Results: Forty-for patients were studied over six months. All patients had vitamin D deficiency. The 28-day mortality in patients with 25(OH)D le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
5
1
1
Order By: Relevance
“…According to the study of Murat Haliloglu et al, they reported that the clinical scores (SOFA, CPIS, and CEPPIS) and biomarkers (NT-proBNP, PCT) were negatively correlated with 25(OH)D levels in all study groups. Unlike our study their results declared the 28-day mortality in patients with 25(OH)D levels ≤ 10 ng/mL was significantly higher than in patients with 25(OH)D > 10ng/mL, that may be related to their cut-off point (10ng/mL) [19]. Amrein et al demonstrated that critically ill patients with low PTH or serum calcium levels, as well as low 25(OH)D levels (cut-off 12 ng/mL) were all at significantly greater risk for all-cause mortality [20].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…According to the study of Murat Haliloglu et al, they reported that the clinical scores (SOFA, CPIS, and CEPPIS) and biomarkers (NT-proBNP, PCT) were negatively correlated with 25(OH)D levels in all study groups. Unlike our study their results declared the 28-day mortality in patients with 25(OH)D levels ≤ 10 ng/mL was significantly higher than in patients with 25(OH)D > 10ng/mL, that may be related to their cut-off point (10ng/mL) [19]. Amrein et al demonstrated that critically ill patients with low PTH or serum calcium levels, as well as low 25(OH)D levels (cut-off 12 ng/mL) were all at significantly greater risk for all-cause mortality [20].…”
Section: Resultscontrasting
confidence: 99%
“…A study to investigate the association of baseline and synthetic vitamin D level, with mortality in critically ill inpatients in ICU, demonstrated that it was the same in patients with 25(OH) D deficiency and in those without such deficiency [17]. However, a study reported that SOFA Score on days 4 and 7 was higher in the group with serum 25(OH) D levels ≤ 10 than in another group [19]. As an index of predicting mortality of critically ill patients [26], SOFA Score can be influenced by several environmental and physiological factors, which may confound the findings of the current study.…”
Section: Resultsmentioning
confidence: 99%
“…From our screens against A. baumannii, calcitriol and calcipotriene, both of which are vitamin D supplements, were identified to control infection in macrophages. Interestingly, vitamin D deficiency has been linked to the development of A. baumannii infections and is a predictor of mortality in critically ill patients (54,55). In terms of its mechanism of action, vitamin D has been reported to induce the antimicrobial peptide LL-37, which can effectively kill both Gram-positive and Gram-negative pathogens as well as promote bacterial phagocytosis and killing by macrophages (56).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous and diverse underlying systemic diseases have been reported as potential risk factors for mortality in A. baumannii infection (19)(20)(21)(22)(23)(24). These include malignancy, post-transplantation status and chronic respiratory disease following previous survey.…”
Section: Discussionmentioning
confidence: 99%